The Rising Incidence of Acne Vulgaris in Adolescents: Lifestyle Factors and Preventive Strategies in Bangladesh - Prakesh, Utter; Mahmood Abbas (Scientific Journal of Dermatology and Venereology, 2025)
Introduction: Acne vulgaris, a common skin condition, significantly impacts adolescents' quality of life. In Bangladesh, the prevalence of acne vulgaris has been increasing, particularly among urban adolescents. This study aims to investigate the lifestyle factors associated with acne vulgaris and explore potential preventive strategies. Methods: A cross-sectional study was conducted among 400 adolescents (aged 12-18 years) in Dhaka, Bangladesh. Data were collected using a structured questionnaire, including sociodemographic information, dietary habits, sleep patterns, stress levels, and skincare practices. Acne severity was assessed using the Global Acne Grading System (GAGS). Statistical analyses were performed to identify associations between lifestyle factors and acne severity. Results: The prevalence of acne vulgaris was 68.5%. A significant association was found between acne severity and high glycemic index (GI) diets (p<0.01), irregular sleep patterns (p<0.05), and high stress levels (p<0.001). Inadequate skincare practices, such as infrequent face washing and the use of comedogenic cosmetics, were also associated with increased acne severity (p<0.05). Conclusion: This study highlights the significant impact of lifestyle factors on acne vulgaris in Bangladeshi adolescents. Interventions targeting dietary habits, sleep patterns, stress management, and skincare practices may be effective in preventing and managing acne vulgaris in this population.